Covid-19 Vaccines, Innovation, and Intellectual Property Rights - Guido Cozzi; Silvia Galli (Global Labor Organization (GLO), 2022)
Should the intellectual property rights on the first Covid-19 vaccines be temporarily lifted in applying the Trade-Related Aspect of Intellectual Property (TRIPS) flexibility? Is it right to grant the first generation of Covid-19 vaccines a special treatment from an IPR perspective? On what grounds? By extensively reviewing the available medical and economic literature on the subject, this chapter will guide the reader step-by-step to the leading scientific, political, and cultural challenges in granting broad worldwide access to vaccination. The accumulated delays in providing effective Covid-19 vaccine intervention in the low- and middle-income countries are ultimately responsible for the virus circulation at the global level and the proliferation of immunity-escaping variants. Therefore governmental rationality around the world would suggest any possible active policy tool to scale up the current vaccines supply. However, not to prevent future investment in R&D, the governments should bear the cost of the expected increased industry obsolescence determined by a temporary patent waiver; this includes public patent-buy-outs and regulated public-private R&D partnerships.
Keywords: I18; O30; 330; Vaccines; Covid-19; Pandemics; Patents; Innovation